2014
DOI: 10.1111/iji.12160
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐ and anti‐inflammatory cytokine gene single‐nucleotide polymorphisms in inflammatory bowel disease

Abstract: Anti-inflammatory cytokines have an important role in disease, tumour and transplant processes. Alterations in the regulation of several cytokines have been implicated in a variety of inflammatory disorders, including IBD (inflammatory bowel disease) [Crohn's disease (CD) and ulcerative colitis (UC)]. Cytokine polymorphisms are also known to affect the level of gene expression. Thus, the aim of this study was to determine the relationship between cytokine polymorphisms and the IBD pathologies in a Spanish popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Although these results could enhance the understanding of the development and the clinical behavior of patients, other recent and similar studies have not reported any relationship between IL-1 gene cluster polymorphisms and IBD in populations of different ethnic origin [5,6,9].…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Although these results could enhance the understanding of the development and the clinical behavior of patients, other recent and similar studies have not reported any relationship between IL-1 gene cluster polymorphisms and IBD in populations of different ethnic origin [5,6,9].…”
mentioning
confidence: 65%
“…Other members of IL-1 family have also been implicated in epithelial regeneration and mucosal wound healing (such as IL-33), in bowel inflammation and homeostasis (such as IL-36), and for potent anti-inflammatory activity (such as IL-37) with the ability to downregulate colitis. Polymorphisms of these genes are implicated in intestinal pathology [3][4][5][6].…”
mentioning
confidence: 99%
“…Previous studies were able to find association between CD susceptibility and the IL‐10 promoter polymorphism in Mexican (Garza‐González et al ., ), New Zealand (Wang et al ., ) and United Kingdom (Tagore et al ., ) population. On the other hand, no association was found between the IL‐10 ‐1082 G/A polymorphism with CD or UC in Caucasians of United Kingdom (Koss et al ., ), Korean (Kim et al ., ), Canadian (Sanchez et al ., ), German (Klein et al ., ), Danish (Perrey et al ., and Andersen et al ., ) and Spanish population (Vatay et al ., ; Mendonza et al ., ; López‐Hernández et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…However, other studies in Australian (Fowler et al ., ), Canadian (Zipperlen et al ., ), Korean (Yang et al ., ), Caucasians (Koss et al ., ), Spanish (González et al ., ; López‐Hernández et al ., ) and Iranian (Nosratollah et al ., ) population found that rs1800629 promoter polymorphism was not associated with risk of Crohn's disease. In this sense, our results are in agreement with these data because the association between CD and controls was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Several SNPs have been described for IL1 genes and among these are IL1A −889 , IL1B −511 , IL1R1 pst1 1970 and IL1RA mspa1 11100 SNPs. Studies in CD and UC patients of different ethnicities have reported different correlations with the two forms of IBD, but some of them suggested that these polymorphisms may play a role in etiopathogenesis of IBD [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%